(3QSGdI GdHfGJ GdcHjQIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HdZfi CjJgG GdHfGJ GdUGdMGJ GdeDefGJ GdUjfGJ Cfcf CUZjJf Edi cdGe GdeSJRjOI GdRfOjbI GdeGQbI hGTJYdJ bdhHcf HcPd GdhbMI GdaGSbI s
(3BNQgG (B:s
(3Ydi ef bQCgG Hjf jOi TGc ajgG Ch eNGda dgG JeJ GdQSGdI HMeO ehdGfG SHMGfg hGdTcQ dhdjg GdgGOi GdEeGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B82s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds